On finite-dimensional approximation of solutions of ill-posed problems - Urumbaev, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We show that the modified method for finite-dimensional approximation of solutions of Fredholm integral equations of the first kind presented in this paper is more economical than traditional methods for finite-dimensional approximation.